2021
DOI: 10.1039/d1fo01200b
|View full text |Cite
|
Sign up to set email alerts
|

An arabinogalactan from Lycium barbarum attenuates DSS-induced chronic colitis in C57BL/6J mice associated with the modulation of intestinal barrier function and gut microbiota

Abstract: Ulcerative colitis (UC) is an incurable chronic inflammation of the enteric tract. The aim of this study was to investigate the protective effects of arabinogalactan from Lycium barbarum on DSS-induced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…28,29 Our previous studies indicated that LBP-3 relieved the symptoms (e.g., diarrhea and weight loss) of DSSinduced colitis in mice, which was associated with the composition and diversity of gut microbiota. 17 However, little is known about how the gut microbiota affects the metabolic changes in chronic colitis mice after supplementation with arabinogalactan from L. barbarum. Herein, besides considering specific organisms of the microbiome, untargeted and targeted LC-MS metabolomics in feces were performed to investigate the metabolome and metabolic pathways altered by LBP-3, elucidating the possible mechanism of LBP-3 against UC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…28,29 Our previous studies indicated that LBP-3 relieved the symptoms (e.g., diarrhea and weight loss) of DSSinduced colitis in mice, which was associated with the composition and diversity of gut microbiota. 17 However, little is known about how the gut microbiota affects the metabolic changes in chronic colitis mice after supplementation with arabinogalactan from L. barbarum. Herein, besides considering specific organisms of the microbiome, untargeted and targeted LC-MS metabolomics in feces were performed to investigate the metabolome and metabolic pathways altered by LBP-3, elucidating the possible mechanism of LBP-3 against UC.…”
Section: Discussionmentioning
confidence: 99%
“…LBP-3 ( M w 100 ± 4 kDa) was prepared by our previously reported method. 17 Briefly, the crude polysaccharides were extracted with hot water (80 °C, 2 h) and ethanol precipitation (four times volume of ethanol) from L. barbarum fruits (Ningqi no. 1, Ningxia, China).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations